Pembelajaran Eksperimen Kimia Bagi Siswa Pondok Pesantren Nurul Hakim - Ratna Azizah Mashami; Ahmadi Ahmadi (Indonesian Journal of Education and Community Services, 2024)
Chemistry instruction at the Nurul Hakim Islamic Boarding School (Pondok Pesantren) in Kediri, West Lombok Regency, predominantly relies on lecture-based methods. This approach has led to a lack of deep understanding of chemical concepts among students. Additionally, the limited laboratory facilities have hindered the implementation of practical experiments, which are crucial for enhancing students' comprehension of chemical principles. This community service activity aimed to improve students' learning experiences in chemistry and deepen their understanding of chemical reactions through experimental methods. The activity involved 64 male students from the 10th grade of the Special Education Program. The experimental methods employed in the chemistry lessons enabled students to actively observe, analyze, and apply chemical concepts. Student responses to the experimental learning approach were gathered through questionnaires. The implementation of this community service activity consisted of three stages: preparation, implementation, and follow-up. The results indicated a highly positive response from students, with an average score of 84.8%. The indicator of motivation to learn chemistry achieved the highest score of 90%. These findings suggest that experimental methods are effective in facilitating students' understanding of concepts and increasing their enthusiasm and motivation to learn chemistry. Therefore, experimental methods can be widely implemented to enhance the quality of chemistry education at various levels, particularly in Islamic boarding school environments.